The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.29082/ijnms/2019/vol3/iss3/204
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology Study : Hiv Patient Experience Transvestite to Fulfill Spiritual Need

Abstract: The prevalence of HIV cases increases significantly in the vulnerable population; it is Transvestite. The high prevalence of HIV in transgenders requires treatment and treatment services. However, until now the transgender community is a group that is often not served in various health facilities. Transvestite identity intersections produce unique life experiences, such as multiple identities and spiritual identities. The purpose of the study was to explore the experience of transgender HIV patients when hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…In addition, the oral traditions of the Hadith narrate Allah cursing gender "impersonators" and call for their eviction from the community (Hadith 61: 773, 774). Culturally, transgender Muslims often experience more overt socioreligious persecution than gay, bisexual, or lesbian Muslims, as their more visible gender identity may impact their placement within traditionally gender-segregated Mosques (Kugle, 2010;Pratiwi, Waluyo, Yona, & Susanti, 2019). Historically, there is a complex history of nonbinary gender identities and roles within Islamic and Arabic culture.…”
mentioning
confidence: 99%
“…In addition, the oral traditions of the Hadith narrate Allah cursing gender "impersonators" and call for their eviction from the community (Hadith 61: 773, 774). Culturally, transgender Muslims often experience more overt socioreligious persecution than gay, bisexual, or lesbian Muslims, as their more visible gender identity may impact their placement within traditionally gender-segregated Mosques (Kugle, 2010;Pratiwi, Waluyo, Yona, & Susanti, 2019). Historically, there is a complex history of nonbinary gender identities and roles within Islamic and Arabic culture.…”
mentioning
confidence: 99%
“…As the open-ended descriptions of God’s/gods’ gender included above illustrate, for many nonbinary individuals, the idea that a higher power would have a gender is problematic. Thus, an important understanding resulting from this study is that god concepts may not motivate other attitudes or behaviors but rather become divine embodiments of pre-existing morals and values (Nagoshi and Brzuzy, 2010; Pratiwi et al, 2019; Talvacchia et al, 2014). By endowing their gods with their own morality, people sacralize that morality, making it much more difficult to challenge or call into question (Sumerau et al, 2016a).…”
Section: Discussionmentioning
confidence: 92%
“…Halkitis et al, 2009). Much of the prior research on how transgender individuals interact with and experience religion has focused on their experience of rejection by religions (Liboro, 2015; Nynas and Yip, 2012; Rodriguez and Follins, 2012) or, in some instances, how they find ways to integrate their gender and their religion (Graham, 2004; Pratiwi et al, 2019; Rodriguez, 2020). Some scholars and therapists have suggested that it can be beneficial for transgender individuals who want to integrate their gender with religion or spirituality to look beyond Christianity to religious traditions that have embraced nonbinary genders in the past (Ashraf et al, 2023; Bockting and Cesaretti, 2001; Kraemer, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation